Textile effluent toxicity: a scientometric review and bioassay on bioindicators - Vasconcelos, Marina Wust (2021)
The textile effluent is a complex residue, difficult to degrade and contains colored, xenobiotic, recalcitrant and toxic substances. Scientific efforts seek to ensure sustainability in the textile sector, given its social and economic contribution and the environmental risk to aquatic ecosystems. In this context, the present study has the objective to perform a scientometric analysis of the scientific publications on toxicity of textile effluents and to evaluate the lethal concentration and potential toxic effects of the textile effluent on bioindicator species Artemia salina Linnaeus, 1758 (Anostraca: Artemiidae) and Rhamdia quelen Quoy & Gaimard, 1824 Siluriformes: Heptapteridae). A systematic search was performed in the WoS main collection refining papers that expressed toxicity or potential toxic effects of textile effluent. The final set of refined publications was 214 papers from the WoS main collection with an H-index of 43. The countries with the highest rate of publications are India, Brazil, Turkey, Italy, Pakistan, China and South Korea, respectively. Biotechnology can be a means to achieve bioproducts and tools with better degradation performance. Scientometrics shows a ranking of the main keywords, countries, areas of knowledge, journals and papers on toxicity of textile effluents. It also presents the gaps and trends in research on this theme. For the bioassays nauplii of A. salina were subjected to dilutions of the raw and treated textile effluent for 48 h. While R. quelen larvae and juveniles were exposed to concentrations of raw textile effluent for 96 h for acute toxicity (CL50) tests. Juveniles of R. quelen were exposed for seven days to sub-lethal concentrations of raw and treated textile effluent, defined from the LC50. Histological and genotoxic analyses were performed on these seven-day exposures. The raw textile effluent was found to be toxic to the bioindicators studied resulting in LC50-48h of 6.06 % for nauplii of A. salina, LC50-96h of 3.40 % (v/v) for larvae and 13.42 % (v/v) for juveniles of R. quelen. The LC50-48h for A. salina exposed to the treated effluent differed according to the activity of the treatment and circulation of the activated sludge. The biomarker analysis showed different histological and genetic damage, but not significantly different from the negative control. When comparing the effects, the raw effluent showed higher toxicity for all biomarkers analyzed, highlighting the importance and need for an efficient treatment of textile wastewater.